1995
DOI: 10.1097/00004032-199507000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium Body Burdens in Immigrants to Israel from Areas of the Ukraine, Belarus and Russia Near Chernobyl

Abstract: Of the 500,000 immigrants from the former Soviet Union who came to Israel during 1990-1993, about 100,000 are estimated to have come from radiocontaminated areas near Chernobyl. These people were subject to chronic uptake of environmental radiocesium over protracted periods. During October-November 1991, a joint Israeli-Canadian investigation measured radiocesium body burdens in immigrants to Israel from the Ukraine, Belarus, and the southern Russian republic in order to provide factual information on radioces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…We designated communities in areas with 137Cs soil contamination at the level <37 GBq/kM2 as "less exposed" and those with >37 GBq/km2 as "more exposed," based on map data obtained by IAEA (5). This designation has been confirmed by our findings in the '37Cs body burden study (6), as shown in Figure 1. The population sample was stratified into 3 distinct groups by potential exposure: 1) liquidators (47 men and 8 women), persons who worked on ameliorating the consequences of the Chernobyl explosion, 2) 291 males and 397 females who had lived in more exposed areas, and 3) 351 males and 466 females who had lived in the less exposed areas.…”
Section: Methodssupporting
confidence: 83%
“…We designated communities in areas with 137Cs soil contamination at the level <37 GBq/kM2 as "less exposed" and those with >37 GBq/km2 as "more exposed," based on map data obtained by IAEA (5). This designation has been confirmed by our findings in the '37Cs body burden study (6), as shown in Figure 1. The population sample was stratified into 3 distinct groups by potential exposure: 1) liquidators (47 men and 8 women), persons who worked on ameliorating the consequences of the Chernobyl explosion, 2) 291 males and 397 females who had lived in more exposed areas, and 3) 351 males and 466 females who had lived in the less exposed areas.…”
Section: Methodssupporting
confidence: 83%
“…This designation has been confirmed by our findings in the '37Cs body burden study (6), as shown in Figure 1. The population sample was stratified into 3 distinct groups by potential exposure: 1) liquidators (47 men and 8 women), persons who worked on ameliorating the consequences of the Chernobyl explosion, 2) 291 males and 397 females who had lived in more exposed areas, and 3) 351 males and 466 females who had lived in the less exposed areas.…”
Section: Methodssupporting
confidence: 83%
“…(10). All radiocesium body burdens at the time of measurement were too low for any concerns about health (9). However, the whole-body radiocesium measurements of this population demonstrated that it could be divided into comparison groups coming from areas of relatively high or low levels of ground contamination.…”
Section: Introductionmentioning
confidence: 83%